Urejanje prostora in varstvo okolja - v novih občinah - Ogorelec, Breda (Teorija in praksa, 1995)
This article looks at Slovenia's new structure of local government and critically comments, from the point of view of physical planning and environmental protection. In 1994, elections were held for 147 new local authorities. The elections have been completed, but the legal status of only 31 has been resolved; this includes only 4 out of 11 municipal authorities. The new authorities which represent much smaller communities than their predecessors still retain most of the responsibilities of their forebearers, only on a smaller scale. Environmental protection in the local authorities remains neglected and the new authorities do not know how to respond. Spatial planning is clearly recognized by the new local authorities as a major issue. This survey shows that most of them put spatial planning as a target for institutional development. In general, the new authorities are seeking to ensure their historical independence and are reacting against new national legislation which is centralising power, sometimes to the extent of defying it.
Keywords: prostorsko urejanje; varstvo okolja; environmental protection; občine; Slovenia; Slovenija; prestrukturiranje; local government; lokalna samouprava; predpisi